Superman, up in the sky - King, Tom, 1978- (DC Comics, 2020)
"Aliens have kidnapped a young Earth girl from Metropolis, taking her off-planet. Superman goes in pursuit of them, but with each stop along the path, the mystery of who the aliens are deepens, and the Man of Steel is faced with a new task. Is he getting closer to rescuing the girl, or further away? And who is protecting Metropolis in his absence? This galaxy-spanning question poses a moral dilemma for Superman: How much is one life worth compared to the millions back on his adopted planet? How far will he go, what foes will he face, to find that answer?"--